2016
DOI: 10.1590/1678-4324-2016160062
|View full text |Cite
|
Sign up to set email alerts
|

Green Tropical Phytoextracts - Promising Anticancer Alternative

Abstract: The anticancer potential of aqueous extracts of tropical plants Ficus deltoidea and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A study showed the presence of polyphenols and flavonoids such as genistin, alkaloids, and tannins. [ 9 ] A recent published report by Kumari and Dhanalekshmi[ 10 ] also confirmed the presence of phenols, flavonoids, tannins, and saponins in F. deltoidea leaf, stem, and fruit extract. Harun and Musapha[ 11 ] reported the tannins, phlobatannins, flavonoids, saponins, steroids, terpenoids, cardiac glycosides, alkaloids, anthraquinones, and polyphenol in F. deltoidea var.…”
Section: P Hytochemical a Nalysis Of F Icus Deltoideamentioning
confidence: 70%
See 1 more Smart Citation
“…A study showed the presence of polyphenols and flavonoids such as genistin, alkaloids, and tannins. [ 9 ] A recent published report by Kumari and Dhanalekshmi[ 10 ] also confirmed the presence of phenols, flavonoids, tannins, and saponins in F. deltoidea leaf, stem, and fruit extract. Harun and Musapha[ 11 ] reported the tannins, phlobatannins, flavonoids, saponins, steroids, terpenoids, cardiac glycosides, alkaloids, anthraquinones, and polyphenol in F. deltoidea var.…”
Section: P Hytochemical a Nalysis Of F Icus Deltoideamentioning
confidence: 70%
“…[ 22 ] However, aqueous leaf extract of F. deltoidea has shown less cytotoxicity effect. Khan et al [ 9 ] also investigated cytotoxicity effect of water extract of F. deltoidea leaves on prostate cancer cells and found poor activity. Soib[ 23 ] reported the antiproliferative activity at different concentrations of extract of F. deltoidea after 48h against prostate cancer cell line (DU145).…”
Section: P Harmacological P Roperties Of F Icus Deltoideamentioning
confidence: 99%
“…Natural extracts have been studies as potential mitigators of prostatic disorders, showing anticancer, antiproliferative, antiapoptotic properties [23,24]. The Jaboticaba (MYRTACEAE Myrciaria jaboticaba (Vell.)…”
Section: Introductionmentioning
confidence: 99%
“…Labisia pumila is a herbaceous plant with creeping stem which belongs to Myrsinaceae family ( 12 ) is known by the locals as Kacip Fatimah and Selusuh Fatimah . In Malaysia, there are three varieties: L. pumila var .…”
Section: Introductionmentioning
confidence: 99%